2010
DOI: 10.1002/jor.21081
|View full text |Cite
|
Sign up to set email alerts
|

Radial shock waves effectively introduced NF‐kappa B decoy into rat achilles tendon cells in vitro

Abstract: The purpose of this study was to test if radial shock waves could enhance the introduction of nuclear factor-kappa B (NF-kB) decoy oligodeoxynucleotides, which is reported to markedly inhibit NF-kB activation and suppress pro-inflammatory cytokine gene expression, using rat Achilles tendon cells. In the presence of NF-kB decoy labeled with or without fluorescein isothiocyanate (FITC) in culture media, radial shock waves were applied to the tendon cells in variable conditions and cultivated for 24 h. The transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…As a transcription factor, NF-κB represents a key mechanism for regulating the expression of multiple inflammatory genes. Hence, the suppression of NF-κB activation may account for the clinically beneficial action on tissue inflammation ( 141 ). It is believed that NF-κB activation in the nervous system could be inhibited by ESWT ( 142 ), which subsequently downregulates NF-κB and NF-κB-dependent inflammatory genes such as TNF-α and IL-1, thus leading to the modulation of the whole inflammatory process ( 132 , 143 145 ).…”
Section: Cellular and Molecular Mechanismmentioning
confidence: 99%
“…As a transcription factor, NF-κB represents a key mechanism for regulating the expression of multiple inflammatory genes. Hence, the suppression of NF-κB activation may account for the clinically beneficial action on tissue inflammation ( 141 ). It is believed that NF-κB activation in the nervous system could be inhibited by ESWT ( 142 ), which subsequently downregulates NF-κB and NF-κB-dependent inflammatory genes such as TNF-α and IL-1, thus leading to the modulation of the whole inflammatory process ( 132 , 143 145 ).…”
Section: Cellular and Molecular Mechanismmentioning
confidence: 99%
“…In addition, p65 translocates from the cytoplasm to the nuclei and binds to major target genes, thereby activating the classic NF‐κB pathway . Some researchers believe that TLR4–NF‐κB signaling may be a therapeutic target for treatments . Shen et al investigated the effect of selenomethionine on LPS‐induced inflammatory responses and found inhibition of TNF‐α and cyclooxygenase 2 expression with selenomethionine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…36,40 Some researchers believe that TLR4-NF-jB signaling may be a therapeutic target for treatments. [41][42][43] Shen et al 26 investigated the effect of selenomethionine on LPS-induced inflammatory responses and found inhibition of TNF-a and cyclooxygenase 2 expression with selenomethionine treatment. Furthermore, selenomethionine alleviated the degradation of IjBa and the translocation of p50.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB signaling pathway has been regarded as a typical proinflammatory signal transduction pathway, the activation of which is involved in the regulation of multiple genes, including proinflammatory cytokines, chemokines, adhesion molecules, and enzymes (17,18). It has been reported that blocking the activation of NF-κB signaling pathway in tendon disorders has been more effective than completely inhibiting all the inflammatory response (19)(20)(21). Nevertheless, there is currently insufficient mechanistic understanding of the NF-κB signaling pathway in tendon disorders to manifest this possibility in practice.…”
Section: Introductionmentioning
confidence: 99%